Understanding the determinants of adolescent nutrition in Bangladesh - Leroy, Jef L.; Ruel, Marie T.; Sununtnasuk, Celeste; Ahmed, Akhter (Wiley, 2018)
Evidence on the nutritional status and diets of adolescents in low‐ and middle‐income countries is scant. We characterized the nutritional status (body mass index Z‐scores (BMIZs)) and nutrient intakes of adolescent boys and girls in rural areas in Bangladesh using the 2011–2012 BIHS data, used regression models to identify the socioeconomic determinants of these outcomes, and household fixed effects models to assess whether the gap between boys and girls changed with women's education and empowerment and household wealth. The adolescents’ BMIZ and adequacy of their nutrient intakes were suboptimal. Gender differences varied by outcome and were not systematically in favor of boys. Household wealth was associated with higher BMIZ and probability of adequate energy and micronutrient intakes. Women's education and empowerment were mostly not associated with the study outcomes and did not modify gender differences. There is an urgent need to invest in improving the diets of adolescent boys and girls in Bangladesh. The limited role of women's education and empowerment in improving adolescent nutrition suggests that resources may be too constrained. It may also reflect deeply rooted beliefs about adolescent nutrition and differences between boys and girls that would need to be addressed to improve their nutrition.